Problem Based Learning (PBL) Learning Model Of Indonesian Learning Outcomes For Class II SD Students - Nurul Istiqomah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The aim is to improve learning outcomes of Indonesian language material listening to conversational texts related to culture, sorry. Problem based learning model for second grade elementary school students. This type of research is a class research group, the research subject of teachers and students. Sources of data used are: students, teachers, principals, notes/documents of observations, learning outcomes tests. Data collection techniques with observation (observation), documentation, and tests. The results of this study indicate an increase in Indonesian language learning outcomes. This can be seen from the average value of 76.9 in the first cycle, with a learning completeness percentage of 70% 16 students who completed their studies. Then there was an increase in the class average score of 82.2 in the second cycle, with a percentage of learning completeness 87%, students who finished learning asthma as many as 20 students. The conclusion is that the problem based learning model can improve learning outcomes of Indonesian language material. Listening to text conversations related to culture, apologize to second grade elementary school students.